Bentuk-Bentuk Kesalahan Berbahasa pada Teks Iklan Berbahasa Jawa Karya Siswa Kelas XI SMA Negeri 1 Kartasura - Rosidah, Anik Nur; Waluyo, Budi; Rahadini, Astiana Ajeng (Universitas Sebelas Maret, 2022)
This study aims to describe the forms of language errors in Javanese advertising texts by class XI students of SMA Negeri 1 Kartasura. This research is a qualitative descriptive. The data studied were all words, phrases, clauses, and sentences in the students' Javanese ad text. The source of the data used comes from the advertisement text documents of students. The researcher used purposive sampling technique to determine the sample. In collecting the data, the researcher used assignments and document analysis. Test the validity of the data using data triangulation and theory triangulation. The researcher used an interactive analysis model that consists of three major phases of data analysis, they were data collection, data reduction, data presentation, and conclusions. The results of this study are the forms of language errors in the Javanese advertising text by class XI students of SMA Negeri 1 Kartasura are classified into three levels. First, language errors at the level of spelling (phonology) are 52 or 61,9% which consist of changes in phoneme vowels, changes in consonant phonemes, reduction of phonemes, and addition of phonemes. Second, language errors at the diction/word (morphology) level are 26 or 30,9% consisting of errors in word selection and formation. Third, language errors at the sentence level (syntax) are 6 or 7,1% consisting of incomplete sentence and illogical sentences.